Electronic state dependence of heterogeneous electron transfer: injection from the S1 and S2 state of phlorin into TiO2. Issue 12 (27th February 2015) - Nieto-Pescador, Jesus; Abraham, Baxter; Pistner, Allen J.; Rosenthal, Joel; Gundlach, Lars
Abstract : Similar heterogeneous electron transfer times, from different electronic states of a porphyrinoid into TiO2, suggest that the transfer process involve intermediate transition states not directly related to the steady bulk or surface density of states. Abstract : Ultrafast time-resolved measurements were performed on a novel pentafluorophenyl substituted 5, 5-dimethyl phlorin derivative in solution and when attached to TiO2 colloidal films. The complex excited state dynamics of this porphyrinoid after S1 and S2 excitation was compared at different wavelengths and can be assigned to several subsequent relaxation mechanisms. The difference between excited state dynamics in the free molecule and when attached to an electron accepting electrode was measured. For both cases the dynamics was compared after excitation to the S1 and the S2 state. For the free molecule in solution an intermediate relaxation step was identified and assigned to a buckling motion of the tetrapyrrole ring. On the electrode, heterogeneous electron transfer (HET) times from both states were very similar and around 50 fs. Surprisingly, the large difference in the density of acceptor states that are resonant with the respective donor level of the molecule does not significantly influence HET dynamics. This result indicates that HET proceeds into intermediate transition states that are different from steady state surface states obtained from experiments or computations. The density of states (DOS) of these transient acceptor states appears not to be directly related to the corresponding surface or bulk DOS.